2010
DOI: 10.1111/j.1476-5381.2009.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐synaptic receptors and transporters involved in brain functions and targets of drug treatment

Abstract: Beyond direct synaptic communication, neurons are able to talk to each other without making synapses. They are able to send chemical messages by means of diffusion to target cells via the extracellular space, provided that the target neurons are equipped with high-affinity receptors. While synaptic transmission is responsible for the 'what' of brain function, the 'how' of brain function (mood, attention, level of arousal, general excitability, etc.) is mainly controlled non-synaptically using the extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
165
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(169 citation statements)
references
References 364 publications
(370 reference statements)
3
165
1
Order By: Relevance
“…The dense dopaminergic nerve terminal plexus in the striatal cellular networks mainly operates via extrasynaptic/volume transmission [122]. Various subtypes of extrasynaptic dopamine receptors [123][124][125] are located in projection neurons and interneurons as well as on the afferent nerve terminal networks.…”
Section: Extrasynaptic Signalling/volume Signallingmentioning
confidence: 99%
“…The dense dopaminergic nerve terminal plexus in the striatal cellular networks mainly operates via extrasynaptic/volume transmission [122]. Various subtypes of extrasynaptic dopamine receptors [123][124][125] are located in projection neurons and interneurons as well as on the afferent nerve terminal networks.…”
Section: Extrasynaptic Signalling/volume Signallingmentioning
confidence: 99%
“…Monoamine transporter proteins play a fundamental role in limiting the extent of nonsynaptic volume transmission in the central nervous system (Rice and Cragg, 2008;Vizi et al, 2010). Amphetamine-type stimulants target these transporters by acting as substrates and triggering the efflux of monoamine transmitters, especially dopamine (DA) and norepinephrine (NE) (Rothman and Baumann, 2003;Fleckenstein et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates another form of regulation by 5-HT, the volume transmission. This type of nonsynaptic release of modulatory action (Vízi, 1984;Vízi et al, 2010) was also suggested in a number of peripheral organs of Helix (Benedeczky and Halasy, 1988;Elekes, 2000) and in arthropods (see Nässel, 2009). In conclusion, based on the ultrastructure of neuromuscular contacts of 5-HTLIR axon profiles, we suggest that these contacts are involved in nonsynaptic modulatory processes and may play a double role in regulating the developing buccal mass: 1) a localized effect of 5-HT on the muscle cells through the close but unspecialized contacts and 2) a slow volume transmission effect via the wide intercellular space.…”
Section: Ultrastructure Of Neuromuscular Contactsmentioning
confidence: 86%